Nutritional and management strategies to improve reproductive efficiency in beef cattle - Schwartz, Allen Glen (My University, 2026)
Fertility in beef cattle is one of the most economically important and biologically complex aspects of the beef production system. Improving reproductive efficiency requires an integrated understanding of the factors that regulate puberty, gamete quality, and the establishment of pregnancy. This thesis research is designed to address the fertility of male and female beef cattle through supplementation of omega-3 fatty acids on reproductive development, fatty acid profiles, oxidative status, and semen quality in developing beef bulls, and the evaluation of anogenital distance as a physiological phenotype as a predictor of reproductive tract maturity and the outcome of pregnancy in beef females. These two studies provide a comprehensive analysis of how nutrition and indicators of reproductive maturity, such as anogenital distance, contribute to the variation in fertility, offering practical insight for herd-level management. In the first experiment, developing beef bulls (n = 39) were assigned to one of three dietary treatments for an 80-day supplementation period: a control diet with no omega-3 supplementation (CON), a moderate rate of omega-3 inclusion (MOD; 0.22 kg per head daily), or a high omega-3 rate of inclusion (HI; 0.44 kg per head daily). Supplementation effectively altered circulating fatty acid profiles in serum, increasing omega-3 concentrations in the HI group compared with the CON group throughout the study (P = 0.02). Despite the shift in serum fatty acids, no improvements in semen quality traits were observed. Sperm motility during the three breeding soundness exams tended to improve in the HI group compared with the CON group (P = 0.10), with no treatment effect on progressive motility or morphology. Omega-3 fatty acid supplementation did not alter the reactive oxygen species in seminal plasma at the end of the supplementation period. Scrotal development and carcass characteristics were unaffected by treatment, but the MOD group had the most favorable G:F ratio and was significantly different from the CON group (P = 0.04). Supplementation neither enhanced nor impaired many semen and performance metrics throughout the 80-day supplementation period. The second experiment explored the fertility of beef cattle females (n = 2,663) by investigating the anogenital distance as a predictor of pregnancy and the use of reproductive tract score in a subset of heifers (n = 933). Anogenital distance has been proposed as a noninvasive indicator of prenatal androgen exposure and postnatal reproductive maturation in several species, yet limited data are available in beef cattle. Cattle in this study were assigned to quartiles and tertiles based on the anogenital distance for each location, as well as some heifers being assigned a reproductive tract score. Pregnancy outcomes from fixed-time artificial insemination were used to assess the predictive power of anogenital distance and reproductive tract score. Although anogenital distance exhibited natural variation and was associated with developmental traits, the reproductive tract score consistently emerged as the strongest predictor of pregnancy. Heifers with a greater reproductive tract score were more likely to become pregnant through fixed-time artificial insemination. When modeled together, anogenital distance contributed minimal predictive power beyond reproductive tract score, suggesting that anogenital distance alone cannot replace reproductive tract score as a standalone tool for heifer selection. The presence of measurable anogenital distance variation supports the continued exploration of anogenital distance as part of a set of physiological indicators that captures reproductive tract maturation not fully represented by the reproductive tract score. Collectively, these two studies contribute important insight into the biology of fertility in beef cattle. The bull supplementation trial demonstrates that omega-3 fatty acids effectively modify blood lipid profiles, but short-term supplementation did not yield substantial improvements in semen quality or oxidative status. The anogenital distance offers potential for identifying females with a greater probability of becoming pregnant through timed artificial insemination, but the reproductive tract score remains the most reliable tool available for predicting pregnancy outcomes. Integration of nutritional and physiological assessments across sexes underscores the multifactorial nature of fertility and emphasizes the importance of using validated, biologically meaningful indicators to enhance reproductive efficiency in beef cattle production.
Keywords: Reproductive efficiency; Omega-3 supplementation; Developing bulls; Anogenital distance; Reproductive tract score